2014
DOI: 10.1128/aac.00990-13
|View full text |Cite
|
Sign up to set email alerts
|

O 2 -Dependent Efficacy of Novel Piperidine- and Piperazine-Based Chalcones against the Human Parasite Giardia intestinalis

Abstract: dGiardia intestinalis is the most frequent protozoan agent of intestinal diseases worldwide. Though commonly regarded as an anaerobic pathogen, it preferentially colonizes the fairly oxygen-rich mucosa of the proximal small intestine. Therefore, when testing new potential antigiardial drugs, O 2 should be taken into account, since it also reduces the efficacy of metronidazole, the gold standard drug against giardiasis. In this study, 46 novel chalcones were synthesized by microwave-assisted Claisen-Schmidt con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…The antigiardial activity of the novel compounds 23–67 was tested under both anaerobic and microaerobic conditions. According to ( Dunn et al, 2010 ; Bahadur et al, 2014 ), susceptibility of Giardia trophozoites to increasing concentrations of each compound was assessed based on ATP level determination by luminescence. Dose-response curves for each compound were obtained after 48 h-incubation and compared to the data collected under identical conditions with MTZ, the drug of choice for treatment of giardiasis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The antigiardial activity of the novel compounds 23–67 was tested under both anaerobic and microaerobic conditions. According to ( Dunn et al, 2010 ; Bahadur et al, 2014 ), susceptibility of Giardia trophozoites to increasing concentrations of each compound was assessed based on ATP level determination by luminescence. Dose-response curves for each compound were obtained after 48 h-incubation and compared to the data collected under identical conditions with MTZ, the drug of choice for treatment of giardiasis.…”
Section: Resultsmentioning
confidence: 99%
“…When testing new potential antigiardial drugs, it is thus important to take O 2 into account also to attempt identifying antiparasitic compounds that could be fully effective under the more physiological microaerobic conditions in which MTZ efficacy is reduced due to O 2 presence. This issue has been highlighted in a recent study by our groups ( Bahadur et al, 2014 ) in which O 2 , while making MTZ expectedly less effective, was reported to enhance the efficacy of three piperidine/piperazine chalcone derivatives, pre-selected in a screen conducted under anaerobic conditions.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations